Editors' note - Gonçalo Canto Moniz; Jorge Figueira (Joelho)
JOELHO 10 closes the cycle of the second series of “em cima do joelho”. This cycle aimed to put JOELHO in dialogue with the scientific journals on architecture while integrating some of the irreverence that was explored in the first 12 numbers of ecdj. The goal was no more mapping the everyday life of our school of architecture in Coimbra but contributing to the academic debates that were taking place in the architectural field. Women in architecture, Anthropology, Memory, Teaching through Design, Digital, Heritage, Utopias, European City or Reuse were themes identified by us and a group of guest editors that challenged the academic community to participate. Peer reviewed by invited academic experts, the authors struggled to support their arguments or to achieve coherence. On one side, Joelho became more scientific, but on the other side, it was touched by the irony of the artists in the cover, or the joy of the students in the “exhibition” section. To all of them, a big thanks for keeping JOELHO a beautiful object, either in paper or in the digital cloud.